Rue du Cinématographe : la SCAGL côté studio - Carou, Alain (1895, 1998)
Founded in 1908, the SCAGL (specialized in literary adaptations) had a theater of its own built immediately. The letters of its director, partly preserved, allow us to catch a glimpse of a production structure's functioning that priviligied productivity, with the help of an efficient logistics. Actors received most attractive fees. The cohabitation of the SCAGL and the Établissements Pa thé on the same piece of ground in Vincennes found expression in the daily presence of the editor in the society's management of its infrastructure. Extension projects were interrupted by World War I ; they appeared again in a less ambitious form in 1916, but without being achieved because of new economic context.
https://katalog.adlr.link/Record/ai-49-aHR0cDovL2R4LmRvaS5vcmcvMTAuMzQwNi8xODk1LjE5OTguMTMzMw